COVID-19 in Relation to Chronic Antihistamine Prescription - Anna Puigdellívol-Sánchez; Marta Juanes-González; Ana Calderón-Valdiviezo; Helena Losa-Puig; Roger Valls-Foix; Marta González-Salvador; Celia Lozano-Paz; Josep Vidal-Alaball (Microorganisms)
No hospitalizations or deaths occurred in residents with the COVID-19 infection, treated with antihistamines and azithromycin, of two external nursing homes during the first wave. We assessed whether patients receiving chronic antihistamines in our institution showed better clinical evolution. COVID-19 admissions and related deaths in the public Hospital of Terrassa (n = 1461) during the pandemic period (11 March 2020–5 May 2023) and cases (n = 32,888) during the period of full suspicion diagnosis (1 June 2020–23 March 2022) were referred to as the number of chronic treatments (nT) including or not including antihistamines (AntiHm or NOAntiHm), and their vaccination status before the first infection (VAC or NoVAC) in our assigned population (n = 140,681 at March 2020) was recorded. No deaths occurred in patients treated with up to ≤6 nT in the AntiHm group in all ages. A significant reduction in hospital admission was observed in the 2–7 nT groups either below or over 60 years old [Odds Ratio (OR) NoAntiHm/AntiHm = 1.76–1.32, respectively, in NoVAC or VAC (OR = 2.10 overall] and in the older ≥8 nT group (OR = 2.08 in NoVac]. In conclusion, patients with chronic antihistamine prescriptions, alone or with polypharmacy, showed reduced hospital admission and mortality rates, suggesting the safety of antihistamine treatment and the need to confirm its effectiveness in a prospective trial.